Digital supply chain twins: Conceptual clarification, use cases and benefits - Benno Gerlach; Simon Zarnitz; Benjamin Nitsche; Frank Straube (Logistics, 2021)
Background: Digital supply chain twins (DSCT) are gaining increased attention in academia and practice as they emerge as one of the most important trends in logistics and supply chain management (LSCM). Still, there seems to be no common understanding of the term in scientific literature. Moreover, the broad field of LSCM allows for a multitude of feasible application areas and use cases, yet there exists no conclusive list of them as to date. Methods: This study builds upon a systematic literature review of 66 DSCT articles to identify application areas of DSCT in LSCM as well as specific use cases and their respective intended benefits. Results: To start with, the study derives a unified definition of DSCTs, including possible scopes of applications. Afterwards, five application areas of DSCT in LSCM are synthesized as well as 14 individual use cases and their respective intended benefits. Conclusions: The study leads towards a conceptual clarification of DSCT that is of importance for research and practice alike. For managers it additionally provides up-to-date use cases to guide DSCT applications in practice.
Keywords: 650; digital supply chain twin; digital twin; logistics; logistics and supply chain management; supply chain management; systematic literature review